Tabu annealing: an efficient and scalable strategy for document retrieval. (13th August 2009) - Latha, K.; Rajaram, R.
This paper implements clustering algorithm to the convergence of solution space for large sets of text documents and applies retrieval methodologies to find the information of interest. We propose tabu annealing, a heuristic approach which is a combination of tabu search and simulated annealing with clustering approach. The results of the proposed approach are superior to simulated annealing and tabu search in terms of precision, recall, F-measure, mean fitness, search space and time complexity.